Tiller Dynamics, Leaf Area and Spad Meter Ofrice Varieties Influenced by Different Spacing Under Semi-Dry Condition - Ajmal, K. K.; Fathima, P. S.; Murthy, K. N. Kalyana; Ganapathi, S.; Denesh, G. R.; Prakash, S. S. (International Journal of Economic Plants, 2023)
The field experiment was conducted at College of Agriculture, (V. C. Farm), Mandya, University of Agricultural Sciences, Bengaluru, Karnataka, India during kharif, 2019 and 2020. Soil from experimental site was under sandy loam in texture with 70.50, 15.80 and 13.70% sand, silt and clay, respectively. Soil was alkaline in reaction with pH of 9.02 and low in electrical conductivity (0.37 dS m-1). The fertility status of the soil at experimental site was low in organic carbon (0.39%), available nitrogen (182.12 kg N ha-1) and available potassium (122.32 kg K2O ha-1), however it was high in available phosphorus (78.74kg P2O5ha-1). Results indicated that maximum leaf area, SPAD meter reading and tiller production at different days observed in narrow spacing (20 cm row spacing) compared to wider row spacing (30 cm row spacing). Among the different varieties tested, significantly higher leaf area, SPAD meter reading and tiller production was recorded in KMP- 175 and Rasi compared to other varieties.